FACTORS RELATED TO MOTORCYCLING PERFORMANCE OF THE ELDERLY: A CASE STUDY OF KHI LEK SUBDISTRICT, UBON RATCHATHANI PROVINCE, THAILAND - Laksanee BOONKHAO; Pirawan WINTACHAI; Supasinee PONGAREE; Pongsak RATTANACHAIKUNSOPON; Warisin BAUKEAW; Wannee KAEWSUK; Thitima SAENRUEANG (Scientific Journal of Silesian University of Technology. Series Transport)
Thailand had a decline in traffic fatalities even though the estimate is only approximate. This study aims to examine the factors related to the motorcycling riding performance of 69 motorcyclists aged 60 and older in Khi Lek Subdistrict, Muang District, Ubon Ratchathani Province. Data were collected from interviews on driving behavior with the participants and their driving performance from the tests modeled on the Thai driving license test. Fisher’s Exact Test was used to analyze the data. The results showed that the elderly exhibited good motorcycle driving behavior (91.30 %); however, their riding ability was at the level of “need to be improved” (85.51%). They showed poor performance on the reflex test (72.46%) and the depth perception test (69.57%). The tests the participants passed were the color blindness test (100%) and the peripheral vision test (61.82%). This study also found that the average daily motorcycle driving distance (p-value = 0.045) and motorcycle driving experience (p-value = 0.036) of the older motorcycle riders were determined to be statistically significant factors. The findings are useful for responsible organizations to decide on road safety policies to lower the risks of accidents involving elderly motorcycle riders in Thailand. They could consider revoking lifetime driver’s licenses, providing training to promote safe driving techniques, and taking into account how the elderly’s riding performance is correlated to their average daily driving distance and driving experience.